The Fundamentals of Good Writing - Pearsall, Thomas E. and Cunningham, Donald H. (New York Macmillan Publishing Company, 1988)
A handbook for teaching you the fundamentals of good writing. Guides you through the different stages of writing, including in brief: brainstorm, research, compose, revise, and edit.
Keywords: Writing